PENTINGNYA MENJAGA KESEJAHTERAAN EMOSIONAL LANSIA JANDA/DUDA DI PANTI SOSIAL: PERAN LONELINESS DAN DEPRESI - Alne Vitayala; Nasya Putri Nariswari; Syahnur Rahman (PSIKOWIPA (Psikologi Wijaya Putra), 2023)
Many elderly choose to live in nursing homes because they do not receive attention from their families. Loneliness that is felt in nursing homes can affect the mental health of the elderly. This research has high urgency because it describes the negative impact of loneliness (loneliness) on the level of depression in the elderly who are widows/widowers who live in social institutions. In a social context that often lacks attention to this population, this research is important to identify problems and direct attention to efforts to prevent and treat their mental health problems. This study aims to examine the relationship between loneliness (loneliness) and the level of depression in the elderly who are widows/widowers in social institutions. This study uses the literature study method by taking two national articles and three international articles as references. The results show that there is a positive and significant relationship between loneliness and the level of depression in the elderly with widow/widower status in social institutions.